Impacts of soil and water conservation practices on crop yield, run-off, soil loss and nutrient loss in Ethiopia: review and synthesis - Adimassu, Zenebe; Langan, Simon J.; Johnston, Robyn M.; Mekuria, Wolde; Amede, Tilahun (Springer, 2017)
Research results published regarding the impact of soil and water conservation practices in the highland areas of Ethiopia have been inconsistent and scattered. In this paper, a detailed review and synthesis is reported that was conducted to identify the impacts of soil and water conservation practices on crop yield, surface run-off, soil loss, nutrient loss, and the economic viability, as well as to discuss the implications for an integrated approach and ecosystem services. The review and synthesis showed that most physical soil and water conservation practices such as soil bunds and stone bunds were very effective in reducing run-off, soil erosion and nutrient depletion. Despite these positive impacts on these services, the impact of physical soil and water conservation practices on crop yield was negative mainly due to the reduction of effective cultivable area by soil/stone bunds. In contrast, most agronomic soil and water conservation practices increase crop yield and reduce run-off and soil losses. This implies that integrating physical soil and water conservation practices with agronomic soil and water conservation practices are essential to increase both provisioning and regulating ecosystem services. Additionally, effective use of unutilized land (the area occupied by bunds) by planting multipurpose grasses and trees on the bunds may offset the yield lost due to a reduction in planting area. If high value grasses and trees can be grown on this land, farmers can harvest fodder for animals or fuel wood, both in scarce supply in Ethiopia. Growing of these grasses and trees can also help the stability of the bunds and reduce maintenance cost. Economic feasibility analysis also showed that, soil and water conservation practices became economically more viable if physical and agronomic soil and water conservation practices are integrated.